Nanofiber gradient filter cotton and filter material for dust masks
Patent Information
- Application Number
- CN202522037767.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-23
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2035-09-23
AI Technical Summary
但静电吸附力容易受到极性粒子影响,滤棉在使用过程中,随着空气中水分子及极性颗粒物的吸附,静电被中和并逐渐降低,过滤性能下降,影响滤棉的最低过滤效率和实际使用寿命
[0023]1)本实用新型所提供的纳米纤维梯度滤棉和防尘面罩用滤材过滤效率高,其中,所述纳米纤维过滤层提供对0.3µm及以下颗粒的过滤效率高达99.4%。
Smart Images

Figure CN224877186U_ABST
Abstract
Description
Technical Field
[0001] This utility model relates to the field of air filtration materials technology, and in particular to a nanofiber gradient filter cotton and a filter material for dustproof face masks. Background Technology
[0002] Traditional filter cotton mainly uses electrostatic fiber cotton and meltblown cloth as filter materials. The fiber size is in the micron range. Electrostatics are added to the filter material through electret and other means, and the filtration efficiency is improved through electrostatic adsorption to maintain the effectiveness of the product during use.
[0003] Electrostatic fiber cotton and meltblown fabric generally have fiber sizes in the micrometer range, resulting in drawbacks such as high resistance and low filtration efficiency. Current technologies require electrostatic addition to the filter material through electret methods to improve filtration efficiency. However, electrostatic adsorption is easily affected by polar particles. During use, as water molecules and polar particles in the air are adsorbed, the static electricity is neutralized and gradually decreases, leading to a decline in filtration performance and affecting the minimum filtration efficiency and actual service life of the filter cotton. Utility Model Content
[0004] This invention improves the filtration efficiency of filter cotton, extends its service life, and reduces its pressure loss through gradient filtration.
[0005] The technical solution adopted by this utility model to solve the technical problem is:
[0006] A nanofiber gradient filter cotton, comprising, in sequence:
[0007] An electrostatic fiber layer comprising a three-dimensional mesh structure formed by interlacing electrostatic fiber filaments;
[0008] The meltblown layer includes a three-dimensional mesh structure formed by interlaced meltblown fibers. Specifically, the meltblown layer is composed of meltblown fibers that are randomly stacked in space, and the three-dimensional mesh structure formed by the interlacing of the fibers is the meltblown layer.
[0009] The nanofiber filter layer includes a first sublayer, a second sublayer, and a third sublayer. The first, second, and third sublayers comprise a three-dimensional network structure formed by interlaced nanofibers. The first sublayer is in close contact with the meltblown layer. The diameter of the nanofibers in the first sublayer is larger than that in the second sublayer, the diameter of the nanofibers in the second sublayer is larger than that in the third sublayer, and the pore size of the first sublayer is larger than that of the second sublayer, and the pore size of the second sublayer is larger than that of the third sublayer.
[0010] In the aforementioned nanofiber gradient filter cotton, the nanofiber material is one or more of polylactic acid, polyvinylidene fluoride, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl alcohol, polyethylene oxide, polyglycolic acid, polycaprolactone, polystyrene, polymethyl methacrylate, polyvinylidene chloride, ethylene-propylene copolymer, polyvinyl acetate, polyethylene elastomer, polyamide, and copolyamide.
[0011] In the above-mentioned nanofiber gradient filter cotton, the diameter of the nanofibers in the first sublayer is 200-500 nanometers, and the pore size of the first sublayer is 200-800 nanometers.
[0012] In the above-mentioned nanofiber gradient filter cotton, the diameter of the nanofibers in the second sublayer is 100-200 nanometers, and the pore size of the second sublayer is 100-300 nanometers.
[0013] In the above-mentioned nanofiber gradient filter cotton, the diameter of the nanofibers in the third sublayer is 50-100 nanometers, and the pore size of the third sublayer is 50-200 nanometers.
[0014] In the aforementioned nanofiber gradient filter cotton, the nanofibers of the nanofiber filter layer are loaded in the corresponding sublayers of the nonwoven fabric.
[0015] In the above-mentioned nanofiber gradient filter cotton, the pore size of the electrostatic fiber layer is 0.5-10 micrometers, and the diameter of the electrostatic fiber filament is 5-10 micrometers.
[0016] In the aforementioned nanofiber gradient filter cotton, the pore size of the meltblown layer is 0.5-5 micrometers, and the diameter of the meltblown fiber is 1-5 micrometers.
[0017] In the above-mentioned nanofiber gradient filter cotton, the electrostatic fiber filaments are made of polyester or polypropylene;
[0018] In the aforementioned nanofiber gradient filter cotton, the meltblown fiber is made of polypropylene.
[0019] In the aforementioned nanofiber gradient filter cotton, the total thickness of the nanofiber gradient filter cotton is 1.5-3mm, wherein the thickness of the electrostatic fiber layer is 0.5-1.5mm, the thickness of the meltblown layer is 0.3-0.8mm, and the total thickness of the nanofiber filter layer is 0.3-0.7mm.
[0020] A filter material for a dust mask has a dust filter section on the main body of the dust mask. The dust filter section is made of the above-mentioned nanofiber gradient filter cotton. The dust filter section consists of the nanofiber filter layer, the melt-blown layer and the electrostatic fiber layer from the inside to the outside.
[0021] In the aforementioned dustproof face mask filter material, the dustproof filter part is formed by hot pressing, and the nanofiber filter layer, the meltblown layer and the electrostatic fiber layer are fixed together by hot pressing.
[0022] By employing the above technical solution, this utility model has at least the following advantages:
[0023] 1) The nanofiber gradient filter cotton and dust mask filter material provided by this utility model have high filtration efficiency, wherein the nanofiber filter layer provides a filtration efficiency of up to 99.4% for particles of 0.3µm and below.
[0024] 2) The nanofiber gradient filter cotton and dust mask filter material provided by this utility model have low air resistance. The gradient structure formed by the electrostatic fiber layer, meltblown layer and nanofiber filter layer (including the first sublayer, the second sublayer and the third sublayer) reduces pressure loss and maintains a comfortable breathing experience.
[0025] 3) The nanofiber gradient filter cotton and dust mask filter material provided by this utility model have strong dust holding capacity and extend the service life of the filter cotton through the multi-layer structure, making them suitable for high dust environments.
[0026] The above description is only an overview of the technical solution of this utility model. In order to better understand the technical means of this utility model and to implement it in accordance with the contents of the specification, the preferred embodiments of this utility model are described in detail below with reference to the accompanying drawings. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the structure of the nanofiber gradient filter cotton proposed in this utility model;
[0028] Figure 2 This is a schematic diagram of the structure of the nanofiber filter layer proposed in this utility model;
[0029] Figure 3 This is a comparison chart of the resistance rise curves during the filter cotton loading test of this utility model;
[0030] Figure 4 This is a comparison chart of efficiency curves during the filter cotton loading test of this utility model;
[0031] Figure 5 This is a schematic diagram of the structure of the filter material for the dustproof face mask proposed in this utility model. Detailed Implementation
[0032] To further illustrate the technical means and effects adopted by this utility model in order to achieve the intended purpose of the invention, the following detailed description of the specific implementation methods, structures, features and effects of this utility model application is provided in conjunction with the accompanying drawings and preferred embodiments.
[0033] Nanofiber gradient filter cotton examples
[0034] like Figures 1-4 As shown, this embodiment provides a nanofiber gradient filter cotton, which sequentially includes an electrostatic fiber layer 1, a meltblown layer 2, and a nanofiber filter layer 3. The electrostatic fiber layer 1 is a three-dimensional mesh structure formed by interwoven electrostatic fiber filaments. The meltblown layer 2 is composed of meltblown fibers, which are randomly stacked in space, forming a three-dimensional mesh structure. The nanofiber filter layer 3 includes a first sublayer 31, a second sublayer 32, and a third sublayer 33. The first sublayer 31 is in close contact with the meltblown layer 2. The diameter of the nanofibers in the first sublayer 31 is larger than that in the second sublayer 32, the diameter of the nanofibers in the second sublayer 32 is larger than that in the third sublayer 33, the pore size of the first sublayer 31 is larger than that of the second sublayer 32, and the pore size of the second sublayer 32 is larger than that of the third sublayer 33.
[0035] Each single layer (including sublayers) of this invention is made of a uniform material, and when stacked together, they form a gradient structure, which can be understood as being composed of multiple layers of nanofibers with uniform structures.
[0036] The electrostatic fiber layer 1 has a fiber diameter range of 5-10 micrometers and a pore size range of 0.5-10 micrometers. Its main function is to initially intercept larger particles and provide a certain electrostatic adsorption capacity.
[0037] The nanofiber gradient filter cotton of this invention has a high-efficiency filtration capability for fine particulate matter of PM2.5 and below (i.e., diameter less than 2.5 micrometers). At the same time, it effectively intercepts larger particles through gradient structure to avoid clogging, thus making it suitable for high dust environments.
[0038] In this invention, the fiber diameters of the nanofiber filter layer 3, meltblown layer 2, and electrostatic fiber layer 1 gradually increase. The pore sizes of the electrostatic fiber layer 1, meltblown layer 2, and nanofiber filter layer 3 gradually decrease. This gradient structure intercepts particles of different sizes layer by layer, preventing large particles from clogging the small-pore filter layer at the back end, slowing down the rate of resistance increase during use, and extending the service life.
[0039] The electrostatic adsorption capacity of traditional filter cotton decreases with time, humidity, and the adsorption of polar particles, leading to a decline in filtration efficiency and a shortened service life. The nanofiber filter layer 3 of this invention primarily relies on physical interception, independent of electrostatics. This nanofiber filter layer has finer fibers and smaller pores, and the filtration process is based on physical interception, unaffected by electrostatic decay. Therefore, its filtration performance is more stable and its lifespan is longer.
[0040] In this embodiment, the nanofiber layer has a gradient structure inside. The production process uses electrospinning technology. By adjusting parameters such as spinning voltage, the diameter of the first layer of fibers loaded on the substrate is relatively large to ensure good adhesion to the substrate. Subsequently, the diameter of the loaded fibers gradually becomes thinner and the pore size becomes smaller, forming a gradient structure to intercept particles that are not intercepted by the front electrostatic fiber layer 1 and the meltblown cloth, thereby improving the overall filtration efficiency of the filter cotton and extending its service life.
[0041] In this way, the nanofiber layer in this embodiment provides a filtration efficiency of up to 99.4% for particles of 0.3µm and smaller.
[0042] Specifically, the nanofiber layer in this embodiment has a fiber diameter at the nanometer level. It does not undergo electrostatic electret treatment and primarily intercepts particulate matter through purely physical means. Therefore, it is not affected by water molecules and polar particles, resulting in a longer filtration lifespan. The filter cotton containing the nanofiber layer of this invention can be used continuously for 12 hours, while traditional filter cotton needs to be replaced after 6-8 hours due to excessive resistance and breathability.
[0043] The nanofiber layer in this embodiment has a finer fiber diameter, reaching the nanometer level, with small pore size and high porosity, which can maintain high filtration efficiency while maintaining lower airflow resistance.
[0044] Furthermore, as a possible implementation, the nanofiber material may also be one or more of polylactic acid, polyvinylidene fluoride, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl alcohol, polyethylene oxide, polyglycolic acid, polycaprolactone, polystyrene, polymethacrylate, polyvinylidene chloride, ethylene-propylene copolymer, polyvinyl acetate, polyethylene elastomer, polyamide, and copolyamide.
[0045] This embodiment uses three types of nanofiber gradient filter cotton and two types of traditional filter cotton from the prior art as examples. Gradient filter cotton-1 is named as follows: the nanofiber filter layer is made of polyacrylonitrile; gradient filter cotton-2 is named as follows: the nanofiber filter layer is made of polylactic acid; and gradient filter cotton-3 is named as follows: The specific filtration efficiency of the nanofiber gradient filter cotton of this application is further explained. The specific parameters of the three types of nanofiber gradient filter cotton and the traditional filter cotton are as follows:
[0046] 1) Material
[0047]
[0048] ii) Thickness (mm)
[0049]
[0050] 3) Fiber diameter (nm)
[0051]
[0052] (iv) Aperture (nm)
[0053]
[0054] The pore size parameter of this invention refers to the average pore size or effective pore size of the material in the layer.
[0055] Furthermore, as a possible implementation, the diameter of the nanofibers in the first sublayer 31 can also be any value between 200 and 500 nanometers.
[0056] More preferably, the diameter of the nanofibers in the first sublayer is 200-350 nanometers.
[0057] Furthermore, as a possible implementation, the pore size of the first sublayer 31 can also be any value between 200 and 800 nanometers.
[0058] More preferably, the pore size of the first sublayer is 250-450 nanometers.
[0059] Furthermore, as a possible implementation, the diameter of the nanofibers in the second sublayer 32 can also be any value between 100 and 200 nanometers.
[0060] More preferably, the diameter of the nanofibers in the second sublayer is 130-170 nanometers.
[0061] Furthermore, as a possible implementation, the pore size of the second sublayer 32 can also be any value between 100 and 300 nanometers.
[0062] More preferably, the pore size of the second sublayer is 140-170 nanometers.
[0063] Furthermore, as a possible implementation, the diameter of the nanofibers in the third sublayer 33 can also be any value between 50 and 100 nanometers.
[0064] More preferably, the diameter of the nanofibers in the third sublayer is 50-100 nanometers.
[0065] Furthermore, as a possible implementation, the pore size of the third sublayer 33 can also be any value between 50 and 200 nanometers.
[0066] More preferably, the pore size of the third sublayer is 80-90 nanometers.
[0067] Furthermore, the nanofibers of the nanofiber filter layer 3 are loaded onto the nonwoven fabric to form corresponding sublayers. In a specific implementation, the nanofibers are first loaded onto the nonwoven fabric, and then stacked together to form the nanofiber filter layer 3.
[0068] Furthermore, as a possible implementation, the pore size of the electrostatic fiber layer 1 can also be any value between 0.5 and 10 micrometers.
[0069] More preferably, the pore size of the electrostatic fiber layer is 6-9 micrometers.
[0070] Furthermore, as a possible implementation, the diameter of the electrostatic fiber can be any value between 5 and 10 micrometers.
[0071] More preferably, the diameter of the electrostatic fiber is 7-9 micrometers.
[0072] Furthermore, as a possible implementation, the pore size of the meltblown layer 2 can also be any value between 0.5 and 5 micrometers.
[0073] More preferably, the pore size of the meltblown layer is 3-5 micrometers.
[0074] Furthermore, as a possible implementation, the diameter of the meltblown fiber can be any value between 1 and 5 micrometers.
[0075] More preferably, the diameter of the meltblown fiber is 1-3 micrometers.
[0076] Furthermore, in this embodiment, the electrostatic fiber filament is made of polypropylene.
[0077] As a possible implementation, the material of the electrostatic fiber filament can also be polyester.
[0078] In this embodiment, the meltblown fiber is made of polypropylene.
[0079] Although both the electrostatic fiber filaments and the meltblown fiber are made of polypropylene in this embodiment, the electrostatic fiber layer has coarse, long fibers with a relatively loose and porous structure, intercepting large particles larger than 10 micrometers and primarily serving a pre-filtration function. The meltblown layer has finer, more irregularly interwoven fibers and undergoes electrostatic electret treatment, primarily intercepting even smaller particles.
[0080] Furthermore, as a possible implementation, the total thickness of the nanofiber gradient filter cotton can also be any value between 1.1 and 3 mm.
[0081] Furthermore, as a possible implementation, the thickness of the electrostatic fiber layer 1 can be any value between 0.5 and 1.0 mm.
[0082] Furthermore, as a possible implementation, the thickness of the meltblown layer 2 can also be any value between 0.3 and 0.8 mm.
[0083] Furthermore, as a possible implementation, the total thickness of the nanofiber filter layer 3 can be any value between 0.3 and 0.7 mm.
[0084] In specific implementation, as shown in the accompanying drawings of this embodiment, the thicknesses of the first sublayer 31, the second sublayer 32, and the third sublayer 33 are all the same (0.1-0.2 mm).
[0085] As a possible implementation, the first sublayer 31 may be thicker, the second sublayer 32 may be thinner, and the third sublayer 33 may be the same thickness as the second sublayer 32, or the third sublayer 33 may be thinner.
[0086] This embodiment tests five types of filter cotton according to the GB2626-2019 6.3KN type filtration efficiency test method. The instrument used is the Longman LM2626-II mask filtration efficiency resistance test stand.
[0087] The specific testing steps are as follows:
[0088] (1) Fix the test filter cotton sample with a clamp, put it into the test interface of the equipment, and operate the equipment to start the load test.
[0089] (2) During the test, the current filtration efficiency and resistance are measured every 15 seconds and updated in real time on the efficiency curve and resistance curve. The entire test process is carried out automatically by the equipment.
[0090] (3) When the resistance reaches the set value (996Pa), the test will stop automatically.
[0091] (4) After exporting the data, the dust holding capacity and resistance rise curve can be calculated.
[0092] The specific test results are shown in the table below:
[0093]
[0094] The loading test conditions for the five filter cotton samples were kept consistent. The loading test revealed that the dust holding capacity of traditional filter cotton was only 54-90 mg, while that of nanofiber filter cotton could reach 170-200 mg, more than doubling the dust holding capacity compared to traditional filter cotton. Furthermore, based on the resistance rise curve during the loading test (…), Figure 3The comparison shows that traditional filter cotton reaches a resistance of 996 Pa after 34-66 minutes of loading, while nanofiber filter cotton requires 175-180 minutes of loading to reach 996 Pa. This indicates that nanofiber filter cotton has a higher dust holding capacity and a slower rate of resistance increase, which can significantly extend the wearing time in actual use, and does not cause shortness of breath even after long-term wear.
[0095] Example of filter material for dust masks
[0096] like Figure 5 The dustproof face mask filter material shown has a dustproof filter part 11 on the body of the dustproof face mask. The dustproof filter part 11 is made of nanofiber gradient filter cotton as described in the above embodiment. The dustproof filter part 11 consists of the nanofiber filter layer 3, the meltblown layer 2 and the electrostatic fiber layer 1 from the inside to the outside.
[0097] The dust filter can be fixedly connected to the dust mask body to form a dust mask.
[0098] Preferably, as a possible implementation, the dust mask has a replaceable filter element structure, wherein the replaceable filter element is the dust filter section 11.
[0099] Furthermore, the dust filter section 11 is formed by hot pressing, and the edges of the nanofiber filter layer 3, the meltblown layer 2 and the electrostatic fiber layer 1 are fixed together by hot pressing.
[0100] Preferably, the dust filter 11 can be any shape, such as circular, elliptical, square, rhomboid, any symmetrical shape or other irregular shape.
[0101] The above description is merely a preferred embodiment of the present utility model and is not intended to limit the present utility model in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present utility model shall still fall within the scope of the technical solution of the present utility model.
Claims
1. A nanofiber gradient filter cotton, characterized in that, In order, they include: An electrostatic fiber layer comprising a three-dimensional mesh structure formed by interlacing electrostatic fiber filaments; The meltblown layer comprises a three-dimensional mesh structure formed by interlacing meltblown fibers; The nanofiber filter layer includes a first sublayer, a second sublayer, and a third sublayer. The first, second, and third sublayers comprise a three-dimensional network structure formed by interlaced nanofibers. The first sublayer is in close contact with the meltblown layer. The diameter of the nanofibers in the first sublayer is larger than that in the second sublayer, the diameter of the nanofibers in the second sublayer is larger than that in the third sublayer, and the pore size of the first sublayer is larger than that of the second sublayer, and the pore size of the second sublayer is larger than that of the third sublayer.
2. The nanofiber gradient filter cotton according to claim 1, characterized in that, The nanofiber material is polylactic acid, polyvinylidene fluoride, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl alcohol, polyethylene oxide, polyglycolic acid, polycaprolactone, polystyrene, polymethyl methacrylate, polyvinylidene chloride, ethylene-propylene copolymer, polyvinyl acetate, polyethylene elastomer, polyamide, or copolyamide.
3. The nanofiber gradient filter cotton according to claim 1, characterized in that, The diameter of the nanofibers in the first sublayer is 200-500 nanometers, and the pore size of the first sublayer is 200-800 nanometers. The nanofibers in the second sublayer have a diameter of 100-200 nanometers, and the pore size of the second sublayer is 100-300 nanometers. The nanofibers in the third sublayer have a diameter of 50-100 nanometers, and the pore size of the third sublayer is 50-200 nanometers.
4. The nanofiber gradient filter cotton according to claim 1, characterized in that, The nanofibers in the nanofiber filter layer are loaded in the corresponding sublayers formed in the nonwoven fabric.
5. The nanofiber gradient filter cotton according to claim 1, characterized in that, The pore size of the electrostatic fiber layer is 0.5-10 micrometers, and the diameter of the electrostatic fiber filament is 5-10 micrometers.
6. The nanofiber gradient filter cotton according to claim 1, characterized in that, The pore size of the meltblown layer is 0.5-5 micrometers, and the diameter of the meltblown fiber is 1-5 micrometers.
7. The nanofiber gradient filter cotton according to claim 1, characterized in that, The electrostatic fiber filament is made of polyester and / or polypropylene; The meltblown fiber is made of polypropylene.
8. The nanofiber gradient filter cotton according to claim 1, characterized in that, The total thickness of the nanofiber gradient filter cotton is 1.1-3mm, wherein the thickness of the electrostatic fiber layer is 0.5-1.5mm, the thickness of the meltblown layer is 0.3-0.8mm, and the total thickness of the nanofiber filter layer is 0.3-0.7mm.
9. A filter material for a dustproof face mask, wherein a dustproof filter section is provided on the body of the dustproof face mask, characterized in that, The dust filter section is made of nanofiber gradient filter cotton according to any one of claims 1 to 8, and the dust filter section consists of the nanofiber filter layer, the meltblown layer and the electrostatic fiber layer from the inside to the outside.
10. The filter material for a dustproof face mask according to claim 9, characterized in that, The dustproof filter section is formed by hot pressing, and the edges of the nanofiber filter layer, the meltblown layer and the electrostatic fiber layer are fixed together by hot pressing.